1998
DOI: 10.1128/jb.180.12.3250-3252.1998
|View full text |Cite
|
Sign up to set email alerts
|

The Bacillus subtilis AraE Protein Displays a Broad Substrate Specificity for Several Different Sugars

Abstract: Bacillus subtilis 168 is unable to grow on xylose and galactose as sole carbon sources, owing to the lack of specific transporters. We show that they are imported into the cell by the activity of AraE, an arabinose transporter whose synthesis is induced by l-arabinose.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(35 citation statements)
references
References 14 publications
1
34
0
Order By: Relevance
“…While possessing all proteins necessary to degrade D-galactose, B. subtilis 168 1A1 is unable to grow in minimal medium with this sugar as the sole carbon source, owing to the lack of a specific transporter. However, D-galactose is imported when L-arabinose is also added to the minimum medium (Krispin & Allmansberger, 1998). Bacillus subtilis 168 1A1 and two isogenic mutants, BFS2613 or BFS2619 (in which yoxA or dacC had been disrupted, respectively), were grown in M9 medium with 5 mM D-galactose as the main carbon source and 1 mM L-arabinose to induce the AraE transporter synthesis.…”
Section: Growth Of B Subtilis 168 1a1 Bfs2613 and Bfs2619 Strains Imentioning
confidence: 99%
“…While possessing all proteins necessary to degrade D-galactose, B. subtilis 168 1A1 is unable to grow in minimal medium with this sugar as the sole carbon source, owing to the lack of a specific transporter. However, D-galactose is imported when L-arabinose is also added to the minimum medium (Krispin & Allmansberger, 1998). Bacillus subtilis 168 1A1 and two isogenic mutants, BFS2613 or BFS2619 (in which yoxA or dacC had been disrupted, respectively), were grown in M9 medium with 5 mM D-galactose as the main carbon source and 1 mM L-arabinose to induce the AraE transporter synthesis.…”
Section: Growth Of B Subtilis 168 1a1 Bfs2613 and Bfs2619 Strains Imentioning
confidence: 99%
“…Until now, only two mechanisms of D-xylose transport have been characterized in bacteria. One mechanism, identified in Escherichia coli (5,6), Salmonella typhimurium (29), Bacillus megaterium (28), Lactobacillus brevis (1), Bacillus subtilis (12,27), Tetragenococcus halophila (35), and some ruminal bacteria (31,33), involves a D-xylose-H ϩ or -Na ϩ symporter. The second mechanism consists of a high-affinity D-xylose transport system involving a periplasmic binding protein and is driven by ATP.…”
mentioning
confidence: 99%
“…Decreased intracellular xylose concentration would alter the ratio of unbound to xylose-bound XylR repressor, which would promote XylR-mediated repression of the XylR-controlled gene. Reduction of intracellular xylose concentration could be further exacerbated if the predicted sugar/ cation symporter CA_C1339 (araE1) transports both arabinose and xylose, as has been demonstrated for many bacterial pentose transporters, such as in B. subtilis, E. coli, and Salmonella enterica serovar Typhimurium (42,43). Previous transcriptomic data suggested that CA_C1339 (araE1) was a xylose-specific transporter; however, bioinformatic analysis found an AraR binding site in its promoter region, implying a role in arabinose transport as well (19).…”
Section: Discussionmentioning
confidence: 99%